Effects of Work Factors on Employee Performance at TKBM Usaha Karya Cooperative in Surabaya - Kokoh Aditama; Hafidulloh; Gogi Kurniawan; Dani Rohmati (Improvement: Jurnal Manajemen dan Bisnis, 2026)
This study examines the extent to which job status security, organizational communication, work environment, training, and regulatory frameworks influence employee performance at Koperasi TKBM Usaha Karya. Employing a quantitative explanatory design, the research involved all 30 active employees through a saturated sampling technique. Primary data were obtained using a five-point Likert-scale questionnaire and subsequently analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The assessment of the measurement model confirmed that all constructs satisfied the required standards of validity and reliability. Despite several variables demonstrating positive directional relationships, hypothesis testing revealed that job status security, organizational communication, work environment, training, and regulatory factors did not exert a statistically significant effect on employee performance. The coefficient of determination (R² = 0.345) indicates that the proposed model explains 34.5% of the variance in performance outcomes. These findings suggest that, within experience-driven and team-oriented operational settings, structural and formal organizational factors may not constitute the primary determinants of performance. The study highlights the necessity of adopting a contextualized perspective in human resource research and offers managerial insights for developing field-based human resource management strategies. Keywords: Job Status Security, Organizational Communication, Work Environment, Training, Regulation, Employee Performanc